Contribuição à família de conversores CC-CC bidirecionais buck/boost - Nimitti, Fabiano Gonzales (2022)
With the search for clean renewable energies and the growing of the greenhouse gases, there is an increase in the number of electric vehicles and own generation. As most renewable energies are naturally in DC the best way to integrate them is through a DC microgrid, where there is an energy storage system with dual power flux and with that comes the needs for bidirectional converters more efficient with simple operation, high gain, reliability and ease of control. Based on this, this work proposes to present a brief review about some of the non-isolated bidirectional converters that have the necessary characteristics for the application, as well as the proposal of four new topologies based on the classic bidirectional buck/boost converter with simplicity of operation, high efficiency and synchronous and asynchronous mode. To achieve such a goal in the proposed converters, some alteration in the classical converter has been done in way that the input and output can be connected in series, parallel or both, in order to get lower stresses in the components. For the proposed topologies are presented its operating stages, design methodology, static and dynamic modeling, estimated efficiency and control technique. In the end, a 1 kW prototypes was implemented to validate the theoretical evaluations with experimental results.